Methodology for Constructing the Region’s Logistics Infrastructure - Popov, Pavel Vladimirovich; Miretskij, Igor Yuryevich (Economy of Regions, 2019)
The article discusses determining the location of the key logistics infrastructure in regions in order to reduce the distribution network’s costs, increase the region’s transit potential and investment appeal, and integrate the region into the global supply chain. We suggest the methodological approach to developing the models of the region’s logistics infrastructure. It efficiently connects transport and storage networks in the region and allows determining the capacity of the key infrastructure. As the criterion, we consider the total costs of delivering the material flow to the consumer. The method includes two stages. At the first stage, using the regions main socio-economic indicators, we determine the cities and districts, where the placement of the infrastructure will be more profitable. To solve this problem we suggest implementing the two-step cluster analysis, discriminant analysis, and ABC methods. The joint use of those methods allows achieving a coherent result that ensures the optimal choice of areas for locating the main elements of warehouse (distribution center, and distribution and sorting warehouses) and transport networks (car fleets and terminals). The second stage involves geo-referencing of the infrastructure on the administrative territorial units, defined at the first stage. For determining the location and capacity of the distribution and sorting warehouses, we propose to apply mathematicprogramming, using the total costs of the delivery and transshipment of goods as the criterion. For organizing the transport infrastructure, linked to the generated warehouse network, we suggest an approach, which allows minimizing cargo shipping’s costs and car fleet and terminals’ maintenance. To solve the optimization problems we suggest using the method of separable programming and branch-and-bound method. The article demonstrates the appliance of the proposed method on the example of Volgograd oblast. The obtained results can be used to form the regions logistics infrastructure.